Entorno familiar y desarrollo de aprendizaje en niños de 4to grado de la EGB Miguel de Cervantes, parroquia Arcapamba, periodo actual - Aguilar Ochoa, Andy Ramiro (2025)
The project "Family Environment and Learning Development in 4th Grade Children at Miguel de Cervantes EGB, Arcapamba Parish" investigates how the family environment influences children's learning development. It argues that the family is the first and most fundamental educational institution in the development of skills and values; 47% of children in Latin America live in poverty, limiting their access to educational resources. Therefore, the objectives that motivated the research included analyzing theoretical foundations related to the two proposed variables, establishing existing relationships as factors that may influence the learning development of the children under study, and proposing effective strategies to foster a conducive environment for learning. The methodology used is quantitative and descriptive, allowing for the analysis of the relationship between the family environment and children's learning through specific questions that guide the study. Preliminary findings suggest that a positive family environment is related to better learning development in children, while adverse conditions can hinder it. The research aligns with Goal 4 of the 2030 Agenda, which seeks to ensure inclusive and equitable education. In conclusion, this study addresses a relevant local issue and aims to generate a positive impact on the educational community by strengthening the link between home and school, which is essential for fostering a conducive environment for learning and the holistic development of children